Implementasi Quality Function Deployment untuk Meningkatkan Kualitas Jasa Pendidikan di Universitas Islam Riau - Suyadi Suyadi; Hafidzah Nurjannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Competition in higher education institutions requires that these universities must be able to compete with other universities, especially in terms of education services. Where services should be maximized in satisfying students so that our tertiary institutions can be the first choice for students who will continue their studies. The purpose of this study is to find out what attributes are needs and expectations needed by students so that students feel satisfied with the services provided by the university. The population in this study were all active students of the Islamic University of Riau, while the sample selection was performed using Simple Random Sampling techniques of 398 students. The techniques in analyzing the data used are, Kano Model and QFD. The results showed there were 27 attributes, there were 2 answers contained in the canoe model category, including 25 attributes included in the one-dimensional category and 2 attributes included in the attractive category. The quality is still unsatisfactory seen from the calculation of the value of GAP which has 21 negative gap values. From 27 quality attributes, there are 7 priority attributes that need to be improved and there are 10 technical responses that must be improved to meet student satisfaction. Keywords : Quality Function Deployment and Quality of Education Service